A VR Based Anti-accident Training System for Airport’s Power - Gu GuoDong; Mao XinLong; Tang ZhenMin (Institute of Advanced Engineering and Science, 2013)
A virtual environment of airport’s power supply is very useful for anti-accident training. In this paper, an effective method of anti-accident training for airport’s power supply based on Delta3D VR engine was proposed. The architecture of airport’s power supply training system was introduced. The electric closet’s operating simulation was accomplished based on the device’s operation logic. The model of fault and relay protection was designed according to electrical characteristics. A finite automaton model of diesel engine was presented based on operating conditions for virtual operation. Finally, a VR based airport’s power supply system was built and verified in worker’s training. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2501